Sustainable and earthquake resistant structural systems - Coşkun, Erdal; Kıymaz, Güven; SEÇKİN, EDİP (My University, 2010)
Sustainable design, which is one of the most important considerations in anystructural design project nowadays, implies many factors such as environmental friendliness,energy competence, functionality, adaptability and efficient use of world’s resources. Sustainabledesign isnot only the realization of an architect’s vision, but also the notion of the structuralengineering regulation.As a result of close cooperation between architects and structural engineers, many brilliant andelegant structures have been built all over the world in the years. On the other hand, with the increasingconcern over the environment the architects and structural engineers find themselvesonce again faced with new challenges. For example, if a structure is not well designed to surviveextremely devastating earthquakes, in the economical life of the structure, it will either need tobe strengthened or demolished to be rebuilt. Considering the new material which will be consumedfor these operations, the environmental effects will be high from the view point of sustainableconstruction. With this respect, earthquake disaster reduction and sustainable developmenthave equally supportive goals.Technological developments to support earthquake resistant design such as seismic isolations,dampers, durable and flexible structural systems are practical solutions to mitigate the risksagainst earthquake hazards. If properly designed they may lead to structures that are more efficientin materials and also potentially earthquake resistant without the need foreither straighteningor demolishing for rebuilding.The leadership of structural engineers adopting new conceptions of functional and structural design and the related innovative techniques for use in sustainable design and minimizing the environmental impact of structures located in seismic areas will be the main focus of this paper. Also, this paper intends to open the discussion among engineers and architects towards a more active contribution to the use of innovative technology for seismic resistant structure within the context for sustainable construction.